Health literacy in people with venous leg ulcers: a protocol for scoping review. Issue 5 (11th May 2021) - Weller, CD; Team, Victoria; Probst, Sebastian; Gethin, Georgina; Richards, Catelyn; Sixsmith, Jane; Turnour, Louise; Bouguettaya, Ayoub
Abstract : Introduction: Chronic venous leg ulcer (VLU) healing is a complex clinical problem. It requires intervention from skilled, costly, multidisciplinary wound-care teams, working with patients to manage their care. Compression therapy has been shown to help heal venous ulcers and to reduce recurrence, with some evidence suggesting the value of exercise as well. These activities require health education and health literacy (HL) as patients must process, understand and consistently apply health information for successful self-management. Research suggests that those most vulnerable to VLUs also tend to have limited HL, but there have been no reviews examining the state of HL in patients with previous or active VLUs. This scoping review aims to examine the level of HL in VLU patients and how HL may link to self-management behaviours (particularly exercise and compression adherence), and their VLU healing generally. Methods and analysis: We will use Preferred Reporting Items for Systematic Reviews and Meta-Analyses Scoping Review guidelines and the Levac methodology framework to explore eligible papers that examine the effect of HL on their exercise and compression adherence. Electronic databases will be searched (MEDLINE, EMBASE, the Cochrane Library, PsycInfo and Health, OpenGray), examining for all papers on these subjects published between 2000 and 2020. All studies describing compression and or exercise during VLU management will be included. Study characteristics will be recorded; qualitative data will be extracted and evaluated. Quantitative data will be extracted and summarised. Ethics and dissemination: We will disseminate results through peer-reviewed publications. We will use data (ie, journal articles) from publicly available platforms; so, this study does not require ethical review. The consultation step will be carried out with patients, carers and health professionals as part of an established wound consumer group.